A Case of a Malignant Cutaneous Mixed Tumor (Chondroid Syringoma) of the Scapula Treated With Staged Margin-Controlled Excision. (September 2018) - Lal, Karan; Morrell, Travis J.; Cunningham, Michael; O'Donnell, Patrick; Levin, Nikki A.; Cornejo, Kristine M.
Abstract : Abstract: Cutaneous mixed tumor (chondroid syringoma) is the cutaneous counterpart of pleomorphic adenoma of salivary glands, comprised of both epithelial and mesenchymal components. Malignant transformation is exceptionally rare, with only a few cases reported. We report a case of a malignant cutaneous mixed tumor in an 86-year-old white man who presented with a pink indurated plaque on his left scapula. He had a history of nonmelanoma skin cancers, a stage IB malignant melanoma of a lower extremity and Gleason 4 + 3 prostate cancer treated with brachytherapy, external beam irradiation, and bicalutamide. A shave biopsy was performed and histologic examination revealed infiltrative single-unit atypical cells and small ducts in a superficially transected sclerotic dermis suggestive of a poorly differentiated adenocarcinoma. No epidermal connection was identified. Immunohistochemical studies revealed that the tumor was positive for CK7, CAM5.2, and mCEA and negative for CK20, epithelial membrane antigen, P63, prostate-specific antigen, prostatic specific acid phosphatase, and alpha-methylacyl-coenzyme A racemase. A metastasis of the breast or upper digestive tract was favored, although a primary eccrine carcinoma was also considered. Imaging was performed and no other masses were identified. A slow Mohs excision was performed with negative margins. Microscopic examination revealed a biphasic neoplasm comprised of infiltrative epithelial strands and tubules consistent with an eccrine carcinoma in a hyalinized and chondromyxoid stroma within the dermis, arising from a well-circumscribed chondroid syringoma located in the deep dermis and subcutis. Areas of clear cell change, intracytoplasmic vacuolization, and mucin pools were noted. Multiple foci of perineural invasion were identified. Additional immunohistochemical studies revealed that the tumor was positive for S100 and negative for CK5/6, calponin, glial fibrillary acidic protein, GATA3, GCDFP-15, and mammoglobin. Based on the morphologic features and immunoprofile, this was diagnosed as a malignant cutaneous mixed tumor. This case highlights the importance of obtaining adequate tissue for histologic evaluation, as they can be confused with other skin neoplasms because of their clinically ambiguous presentations. Although rare, an accurate diagnosis is important given that long-term follow-up is recommended because of the risk of local recurrence and both lymph node and distant metastases.